ANALISA PRA PENGAJARAN JARAK JAUH (PJJ) PADA MASA PANDEMI COVID 19: Distance Learning;Online Distance Learning;The Covid Pandemic 19;Web-Based Distance Learning. - -, Riswan; -, Nilawati (JURNAL AKADEMIKA, 2020)
Lectures in the odd semester of the 2020/2021 academic year are still carried out by online distance learning, this is done to break the chain of spreading the COVID-19 pandemic which is still high. This PJJ is the second implementation since the COVID-19 pandemic occurred. In facing PJJ in this second semester, researchers tried to examine the readiness of lecturers in implementing PJJ. The data was collected through a questionnaire on the lecturer of the information systems study program and the informatics engineering study program of STMIK Nurdin Hamzah. The questionnaire was made using google form, the response of this application was an analysis researcher, the results showed that the lecturer had prepared the material to be taught. Material preparation refers to the implementation of PJJ last semester, lecturers have also prepared to anticipate the obstacles faced by students in attending PJJ lectures last semester, both obstacles in the internet network, internet quata, assessment, laboratory materials, sending assignments, improving grades. The response data also shows that the preparation of teaching materials that have been prepared by the lecturers is contradicting the needs of the workshop, which are equal to 72.2%. This shows that the material that has been prepared is not optimal, the lecturer wants the material to be varied by paying attention to system design and development, interactivity, active learning, visual imagery and effective communication. It is expected that the same researchers towards this study can expand respondents, and also encourage higher respondent participation.